Ferromagnetic Resonance Studies of Exchange Biased CoO/Fe Bilayer Grown on MgO Substrate - (:unkn) unknown (SPRINGER, 2014)
Dynamic and static magnetizations of an exchange biased bilayer system which is constructed as a proximity of a CoO layer on an Fe-layer grown on the (100) oriented MgO substrate by ion beam sputtering technique have been investigated by ferromagnetic resonance (FMR) and vibrating sample magnetometry (VSM) techniques. The room-temperature FMR measurements reveal that the Fe layer is epitaxially grown on MgO substrate with four-fold magnetocrystalline anisotropy and the hard magnetization axis of the sample is the [100] crystallographic directions of MgO substrate. We have determined the g-value, effective magnetization, magnetocrystalline anisotropy constants and contributions to FMR linewidth due to the intrinsic Gilbert damping and inhomogeneity of magnetization by using Landau-Lifshitz-Gilbert (LLG) equation. We observed an unusual FMR line shape attributed to impedance switching of resonance cavity and complex component of conductivity of sample system. The low-temperature FMR measurement shows asymmetric hysteretic behavior of resonance field related to magnetic coupling of ferromagnetic and antiferromagnetic layers. From both FMR and VSM measurements between 10-300 K, the magnetocrystalline anisotropy is observed to dominate above blocking temperature, while unidirectional anisotropy is observed to dominate below blocking temperature over internal magnetic anisotropy. FMR spectra have a comparatively small linewidth between 40-100 Oe, which indicates to a high crystallinity of the Fe film. Gilbert constant was calculated as 0.007 from the linewidth fitting of FMR spectra. This small value is a suitable for reducing the critical switching current used in magnetic tunneling junction. Detailed exchange bias studies were carried out for hard and easy axis of the sample in the temperature range of 10-300 K. From both low-temperature FMR and VSM measurements, the blocking temperature of the system was determined as similar to 60 K.
Keywords: Magnetic anisotropy; Ferromagnetic resonance; Exchange bias; Antiferromagnetic materials; Gilbert damping parameter; MAGNETIC ANISOTROPIES; FILMS; LINEWIDTH